Impact of additional counselling sessions through phone calls on smoking cessation outcomes among smokers in Penang State, Malaysia - Ali Blebil (BMC Public Health, 2014)
BackgroundStudies all over the world reported that smoking relapses occur during the first two weeks after a quit date. The current study aimed to assess the impact of the additional phone calls counselling during the first month on the abstinence rate at 3 and 6 months after quit date among smokers in Penang, Malaysia.MethodsThe study was conducted at Quit Smoking Clinic of two major hospitals in Penang, Malaysia. All the eligible smokers who attended the clinics between February 1st and October 31st 2012 were invited. Participants were randomly assigned by using urn design method either to receive the usual care that followed in the clinics (control) or the usual care procedure plus extra counselling sessions through phone calls during the first month of quit attempt (intervention).ResultsParticipants in our cohort smoked about 14 cigarettes per day on average (mean = 13.78 ± 7.0). At 3 months, control group was less likely to quit smoking compared to intervention group (36.9% vs. 46.7%, verified smoking status) but this did not reach statistical significance (OR = 0.669; 95% CI = 0.395-1.133, P = 0.86). However, at 6 months, 71.7% of the intervention group were successfully quit smoking (bio-chemically verified) compared to 48.6% of the control group (P < 0.001). The control group were significantly less likely to quit smoking (OR = 0.375; 95% CI = 0.217-0.645, P < 0.001).ConclusionsSmoking cessation intervention consisting of phone calls counselling delivered during the first month of quit attempt revealed significantly higher abstinence rates compared with a standard care approach. Therefore, the additional counselling in the first few weeks after stop smoking is a promising treatment strategy that should be evaluated further.